A North American, single-center experience implanting fenestrated atrial devices and atrial flow regulators into a heterogeneous group of pediatric pulmonary hypertension patients - David Edward Youssef; Konstantin Averin; Konstantin Averin; Susan Richards; Catherine Sheppard; Cameron Seaman; Matthew Pietrosanu; Angela Bates; Angela Bates (Frontiers Media S.A., 2023)
IntroductionThe clinical deterioration commonly experienced by pediatric patients with pulmonary arterial hypertension (PAH) has motivated a shift in the treatment of pulmonary hypertension (PH) through innovations in surgical salvage interventions. The Occlutech fenestrated atrial septal defect (FASD) Occluder and the atrial flow regulator (AFR), which provides a protective, atrial-level shunt during hypertensive crises, have found an important role in treating pediatric patients with PAH. Other groups of pediatric patients with PH may also benefit from a similar protective physiology. The primary aim of this work is to present a single center's experience with AFR and FASD devices for managing a heterogeneous group of pediatric PH patients. A secondary goal is to identify hemodynamic changes and complications following device implantation.Materials and MethodsWe performed a retrospective review of all pediatric PH patients who, after being found suitable, either successfully or unsuccessfully received an FASD or AFR device between January 2015 and December 2021 at the Stollery Children's Hospital in Edmonton, Canada.ResultsFourteen patients (eight female) with a median age of 4.6 (range 0.3-17.9) years and a median body mass index of 15.1 (Q1 = 13.8, Q3 = 16.8) kg/m2 underwent device implantation: five received FASDs, eight received AFRs, and one was ultimately unable to receive an implant due to thrombosed iliac vessels and required surgical intervention. Of the fourteen patients, seven were in group 1 (PAH), one was in group 3 (lung disease), and six were in group 5 (primarily pulmonary hypertension vascular disease) under the World Symposium PH classification. All patients were on mono-, dual-, or triple-drug PH therapy. Device stabilization was not possible for two patients, who then required a repeat catheterization. Of the group 1 patients, three AFR and three FASD implants were successful, while one FASD implant was unsuccessful due to thrombosed vessels. At a six-month clinical assessment, all group 1 patients had patent devices and improved WHO FCs.ConclusionThis work presents a single center's experience with AFR and FASD implants in a heterogeneous group of fourteen pediatric patients with severe PH. This treatment strategy is novel in the pediatric population and so this work provides momentum for future studies of interventional cardiac catheterization procedures for pediatric patients with PH. Further collaborations are required to develop criteria to identify ideal pediatric candidates and optimally time interventions in order to maximize the benefits of this treatment.